2022
DOI: 10.3389/fmicb.2021.814553
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Succession and Organic Pollutants Removal During Olive Mill Waste Sludge and Green Waste Co-composting

Abstract: Olive mill wastewater sludge (OMWS) is the main by-product of the olive industry. OMWS is usually dumped in landfills without prior treatment and may cause several eco-environmental hazards due to its high toxicity, which is mainly attributed to polyphenols and lipids. OMWS is rich in valuable biocompounds, which makes it highly desirable for valorization by composting. However, there is a need to understand how microbial communities evolve during OMWS composting with respect to physicochemical changes and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…following the biodegradation of organic matter [49,50]. This effect was identified in our study (Table 5), with a high content of Ca 2+ in the soil when using OMF formulations.…”
supporting
confidence: 60%
“…following the biodegradation of organic matter [49,50]. This effect was identified in our study (Table 5), with a high content of Ca 2+ in the soil when using OMF formulations.…”
supporting
confidence: 60%
“…A study by Hammad et al [77] showed a significant decrease in maize yield and quality without nitrogen application. Since chlorophyll contents (measured SPAD values) are proportional to the amount of nitrogen present in the leaves [78,79], the decrease in SPAD values over time can be due to nitrogen deficiency in plants. When maize is cultivated in optimal conditions, the plant tends to take up nitrogen (N) during vegetative growth, and this N is later remobilized from leaves to reproductive organs to support kernel formation [80,81].…”
Section: Effects Of Biochar and Amf Treatments On Maize Growth Parame...mentioning
confidence: 99%
“…However, AMF treatments provided new propagules and enhance maize root colonization. It is important to underline that biochar made from woody biomass addition to agricultural soils could increase the AMF spore number in the soil [78,79]. Indeed, when studying the effects of olive waste-based compost, a woodbased biochar, and their combination on soil fertility and maize growth, these authors found that a single application of biochar had a negative impact on mycorrhizal symbiosis after 3 months while the compost gave the best results in terms of mycorrhizal frequency (F%) and intensity of mycorrhizal colonization (M%) and F%.…”
Section: Effect Of Biochar and Amf Treatments On Mycorrhizal Coloniza...mentioning
confidence: 99%